Răspuns :
Răspuns:
1-1/2=1/2
1-1/3=2/3
1-1/4=3/4
.....................
1-1/35=34/35
1-1/36=35/36
√(1-1/2)(1-1/3)(1-1/4)·...·(1-1/35)(1-1/36)=
√1/2·2/3·3/4·...·34/35·35/36=se simplifica numitorul primei fractii cu numaratorul urmatoarei fractii si se obtine
√1/36=1/6
Explicație pas cu pas:
[tex]\sqrt{(1-\dfrac{1}{2})(1-\dfrac{1}{3})(1-\dfrac{1}{4})\cdot\ ...\ \cdot(1-\dfrac{1}{36})}=\sqrt{\dfrac{1}{2}\cdot\dfrac{2}{3}\cdot\dfrac{3}{4}\cdoty\ ...\ \cdot\dfrac{35}{36}}=\sqrt{\dfrac{1}{36}}=\dfrac{1}{6}[/tex]